2018
DOI: 10.1002/slct.201801953
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticle Photocatalysed Degradation of Ibuprofen and Naproxen in Water: Competing Hydroxyl Radical Attack and Oxidative Decarboxylation by Semiconductor Holes

Abstract: The accumulation of pharmaceuticals in the environment is of major concern, and efficient procedures are needed to eliminate them. Inorganic semiconductor photocatalysts, such as titanium dioxide, offer a promising solution. We compare the photocatalytic degradation of the two non‐steroidal anti‐inflammatory drugs ibuprofen (IBP) and naproxen (NPX) by TiO2 nanoparticles in water. Photocatalysts synthesized using different methods were evaluated and compared with commercially available Evonik‐P25 TiO2, and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 92 publications
0
16
2
Order By: Relevance
“…In the latter, photoelectrons are transferred from impregnated TiO2-P25 VB to Cu or V 3d-orbitals lying just below of the CB, then migrate to form O2 -radicals, whereas holes migrate to the surface, react with HOrendering HO radicals, then the so-formed radicals are able to initiate the degradation of the adsorbed phenol molecules (Figure 9). Metal ions with charge different than Ti 4+ could produce oxygen vacancies in the lattice with energy levels below the TiO2-P25 CB (Figure 9), allowing visible light harvesting, acting as active sites for adsorbed water dissociation and capturing holes to diminish electron-hole recombination, thus enhancing the photocatalytic activity [35,[66][67]. Photocatalytic activity, among other factors, is not only dependent on the photogenerated charge carriers trapping, efficient detrap to the surface should also occur.…”
Section: Photodegradation Of Phenol Under Vis and Uv Light Irradiationmentioning
confidence: 99%
“…In the latter, photoelectrons are transferred from impregnated TiO2-P25 VB to Cu or V 3d-orbitals lying just below of the CB, then migrate to form O2 -radicals, whereas holes migrate to the surface, react with HOrendering HO radicals, then the so-formed radicals are able to initiate the degradation of the adsorbed phenol molecules (Figure 9). Metal ions with charge different than Ti 4+ could produce oxygen vacancies in the lattice with energy levels below the TiO2-P25 CB (Figure 9), allowing visible light harvesting, acting as active sites for adsorbed water dissociation and capturing holes to diminish electron-hole recombination, thus enhancing the photocatalytic activity [35,[66][67]. Photocatalytic activity, among other factors, is not only dependent on the photogenerated charge carriers trapping, efficient detrap to the surface should also occur.…”
Section: Photodegradation Of Phenol Under Vis and Uv Light Irradiationmentioning
confidence: 99%
“…This material has been used as a titania standard photocatalyst. Indeed, Evonik P25 remains the most used and efficient photocatalyst under UV light on a large range of molecules [25][26][27][28]. This material is prepared by an aerosol process which involves high temperature treatments (1000-1300 °C) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Atitar et al have reported that Imazapyr shows 5 pKa corresponding to five different ionic equilibria [43]. The adsorption of Imazapyr on the surface of catalyst is accelerated with decreasing the pH of the solution, resulting in stronger and more stable electrostatic interactions, which is expected to enhance the photocatalytic degradation rate of Imazapyr [44]. Carrier et al have reported similar results for photocatalytic degradation of Imazapyr [45].…”
Section: Characterization Of Materialsmentioning
confidence: 91%
“…Compound (2), with m/z = 217 is formed in Pathway IV through decarboxylation of the pyrimidinic ring, confirming oxidation with holes h + , in addition to HO • , as we have recently shown for other compounds possessing carboxylic acid groups. The degradation mechanism involves competition between oxidative decarboxylation of chemisorbed compounds by semiconductor holes, and hydroxyl radical attack on physisorbed substrates [44]. The initial Imazapyr degradation products indicate that Imazapyr adsorbs on the surface of photocatalyst through the carboxylic group [45].…”
Section: Investigation Of the Reaction Products And Reaction Mechanismmentioning
confidence: 99%